DEFENDING ETHICAL NATURALISM: THE ROLES OF COGNITIVE SCIENCE AND PRAGMATISM. - Ward, Andrew (Zygon: Journal of Religion & Science, 2005)
In various essays, Paul Churchland explores the relevance of studies in cognitive science to issues in ethics. What emerges is a kind of ethical naturalism that has two components. The first component is a descriptive-genealogical one whose purpose is to explain how people come to have their ethical beliefs. The second component is a normative one whose purpose is to explain why some values are better than other values. Given this distinction, the problem of integrating ethics with beliefs about the world is a consequence of the traditional view that it is possible to naturalize descriptive-genealogical ethics but not normative ethics. With this distinction as background, I critically examine Churchland's exploration of cognitive science's contribution to our understanding of the values and purposes that should direct our lives. The conclusion is twofold. First, using concepts from the American pragmatists, I argue that, pace Churchland, it is possible to bridge the descriptive-normative gap in order to articulate an ethical naturalism that addresses the so-called naturalistic fallacy but is not committed to an unpalatable relativism. Second, I argue that the sort of ethical naturalism that emerges has affinities to the postmodern ethics of Jean-François Lyotard.